QOL-20. THERAPY ASSESSMENT TOOL FOR LONG TERM SURVIVORS OF PAEDIATRIC CNS MALIGNANCIES. Issue 2 (22nd June 2018) - Graham, Louise; Hodgson, Ailie; Rowen, Elizabeth; Thompson, Sara; Court, Fiona; Heale, Karen; Ryles, Jade; Barlow, Sandra; Halliday, Gail; Watts, Sarah; Bailey, Simon
Abstract: BACKGROUND: Children and young people treated for central nervous system tumours are at risk of developing significant morbidities and complex late effects. NICE guidelines state the management of these morbidities should be provided by a multi-disciplinary team (MDT). Specialist paediatric oncology therapists have wide-ranging skills and knowledge and can holistically manage challenges these children and young people are faced with. Local therapy services can follow-up care but don't have the specialist skills that the principle treatment centre can provide and are restricted by caseload pressures and resources. AIMS: To develop an assessment tool to prioritise and categorise long-term problems affecting function and quality of life. To aid timely and appropriate referrals into local services to improve quality of survivorship. METHOD: Discussion with the MDT to develop a suitable assessment tool and user guide which would identify therapeutic need. Assessment tool piloted and modified to ensure user friendliness and accurate interpretation of answers. Results collected and referral made if need identified. RESULTS: 46 patients were assessed in the first 12 months, 18 of which were identified to have therapeutic needs and referrals into local therapy services were made. Advice and education was provided regarding healthy life style. Encouragement and guidance offered to enable participation in activities of daily life. CONCLUSION: Assessment tool identifies non-medical late effects and results in appropriate and timely further management. Ongoing plan to develop a satellite education day for community services to provide guidance and support on best management for patients to optimise their quality of life.